Effect of Design Parameters on The Separation Efficiency of Vertical Gas/Liquid Separator in Oil Gas Pipeline - AbdulKareem, Lokman A. (Science Journal of University of Zakho, 2014)
The main objective of this work is to size a vertical axis gas liquid separator to separate gas and liquid on a long distance in gas-liquid pipelines. This is necessary to ensure the safe operation of the compressors used along the pipelines.The separator equipped with wave plate demister (vane pack) as the secondary separator.The design is achieved through investigation of the parameters which has an effect on the separation efficiency of the separator. In this study, inlet pipe diameter, vessel bend spacing, vane pack bend angle, momentum breaker, vane pack plate spacing, and the number of bends in pack were used. From the results of this study overall separation efficiency of 99.99% has been achieved.